PARP-1: a critical regulator in radioprotection and radiotherapy-mechanisms, challenges, and therapeutic opportunities - Li, Wen-Hao; Wang, Fei; Song, Gui-Yuan; Yu, Qing-Hua; Du, Rui-Peng; Xu, Ping (Frontiers in Pharmacology, 2023)
Background: Since its discovery, poly (ADP-ribose) polymerase 1 (PARP-1) has been extensively studied due to its regulatory role in numerous biologically crucial pathways. PARP inhibitors have opened new therapeutic avenues for cancer patients and have gained approval as standalone treatments for certain types of cancer. With continued advancements in the research of PARP inhibitors, we can fully realize their potential as therapeutic targets for various diseases. Purpose: To assess the current understanding of PARP-1 mechanisms in radioprotection and radiotherapy based on the literature. Methods: We searched the PubMed database and summarized information on PARP inhibitors, the interaction of PARP-1 with DNA, and the relationships between PARP-1 and p53/ROS, NF-κB/DNA-PK, and caspase3/AIF, respectively. Results: The enzyme PARP-1 plays a crucial role in repairing DNA damage and modifying proteins. Cells exposed to radiation can experience DNA damage, such as single-, intra-, or inter-strand damage. This damage, associated with replication fork stagnation, triggers DNA repair mechanisms, including those involving PARP-1. The activity of PARP-1 increases 500-fold on DNA binding. Studies on PARP-1-knockdown mice have shown that the protein regulates the response to radiation. A lack of PARP-1 also increases the organism’s sensitivity to radiation injury. PARP-1 has been found positively or negatively regulate the expression of specific genes through its modulation of key transcription factors and other molecules, including NF-κB, p53, Caspase 3, reactive oxygen species (ROS), and apoptosis-inducing factor (AIF). Conclusion: This review provides a comprehensive analysis of the physiological and pathological roles of PARP-1 and examines the impact of PARP-1 inhibitors under conditions of ionizing radiation exposure. The review also emphasizes the challenges and opportunities for developing PARP-1 inhibitors to improve the clinical outcomes of ionizing radiation damage.